Ritual Failure : Archaeological Perspectives - Koutrafouri, Vasiliki G.; Sanders, Jeff (Archaeologist) (Sidestone Press, 2013)
'Ritual Failure' is a new concept in archaeology adopted from the discipline of anthropology. Resilient religious systems disappearing, strict believers and faithful practitioners not performing their rites, entire societies changing their customs: how does a religious ritual system transform, change or disappear, leaving only traces of its past glory? Do societies change and then their ritual? Or do customs change first, in turn provoking wider cultural shifts in society? Archaeology possesses the tools and methodologies to explore these questions over the long term; from the emergence of a s.